Sunday at the sunflower inn ebook A heartwarming texas love story. - Thomas, Jodi (2022)
Readers have fallen in love with Jodi Thomas's Honey Creek series, featuring an "inviting setting and quirky, good-hearted characters" ( Publishers Weekly ). With tender romance, adventure, and a touch of mystery, Sunday at the Sunflower Inn is comfort reading at its best, bringing together a cast of endearing locals in intertwined stories perfect for fans of Robyn Carr, Susan Mallery, Susan Wiggs, and Debbie Macomber. Jessica Ann MacKenzie—"Jam" to everyone in Honey Creek—has fulfilled her dream of owning the best restaurant for miles around. Serving romantic candlelit dinners on Valentine's Day is a reminder of another dream, one she's just about given up on. Until, that very night, Sergeant Tucson Smith clambers out of the muddy river and onto her land, bringing the promise of something they've both been searching for. When McCoy Mason crashes on Interstate 45, he doesn't just bust up his Mustang, his leg, and his relationship. He also loses his prospects of a job and apartment in Houston. Honey Creek, home to his estranged grandfather, offers a temporary respite. After all, what permanent use could a town so picture-perfect have for a man like him? At sixty-seven, Charles H. Winston III lives by order and routine. One of his cherished rituals is a regular lunch date with three lovely ladies at the Honey Creek Café, including the very proper Miss Lilly Lambert. But it's not too late to surprise the whole town—or himself—by seizing a chance for a once-in-a-lifetime adventure. And there's no better season than spring, a time of renewed hope and second chances . . .